Knowledge, Attitude, Family Support, and Integrated Health Service Post for Elderly in Working Area of Penurunan Public Health Center Bengkulu - Santoso Ujang Effendi; Nurul Khairani; Susi Hartina (Jurnal Sains Kesehatan, 2018)
The basis for the establishment of integrated health service post for elderly (elderly Posyandu)  was to improve the welfare of the community, especially the elderly. This study aimed to determine the factors that were related to the utilization of  elderly Posyandu in the working area of  Penurunan Public Health Center Bengkulu. This research was conducted in elderly Posyandu in the working area of  Public Health Center Bengkulu in August 2017. This type of research was an analytical survey using a cross sectional design. The population in this study were elderly working area of Penurunan Public Health Center Bengkulu. The sampling technique in this study used proportional random sampling and obtained a sample of 88 elderly people. Data collection in this study used primary data obtained from direct interviews with respondents. Data analysis techniques were carried out by univariate and bivariate analysis with Chi-Square test through the SPSS program. The results were obtained : there were 51 people (58.0%) who did not utilize the elderly posyandu. There were 43 people (48.9%) elderly with good knowledge. There were 45 people (51.1%) elderly who had a Favorable attitude and there were 49 people (55.7%) elderly who received family support. This study showed that there was a significant relationship between knowledge, attitudes, and family support with the utilization of elderly Posyandu in working area of Penurunan Public Health Center Bengkulu. It is expected that the elderly can play an active role in following                  the elderly posyandu activities so that the elderly are more independent and productive and the health status of the elderly can be monitored. Keywords: attitude, elderly posyandu, family support, knowledge,